Knowledge Regarding Self-Administration of Insulin Among the Diabetic Patient Attending the Diabetic Clinic of Tertiary Care Center of Eastern Nepal - Shrestha, D.; Basnet, S.; Parajuli, P.; Baral, D.; Badhu, A. (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Background: Diabetes Mellitus(DM), usually called diabetes or sugar is the condition that occurs when one’s body does not produced enough insulin or body is unable to use normal amount of insulin properly. Objectives: The objectives of this study were to assess the Knowledge and Practice Regarding Self-administration of insulin among the diabetic patient attending the diabetic clinic of BPKIHS, to find out the association between knowledge and Practice with their selected socio-demographic variables and to find out association between knowledge and practice regarding self-administration of insulin. Methods: A descriptive cross-sectional study design was used to conduct the study among the Diabetic patient attending the diabetic clinic of BPKIHS. Data were collected using the self structured questionnaire. Results: The findings revealed that mean knowledge of the participants was 57.55% and practice was 73.98%. Among them 54%(27) of participants has inadequate knowledge, remaining 46%(23) has adequate knowledge. Similarly, 48%(24) of participants has inadequate practice, and remaining 52%(26) has adequate practice. There was significant association of educational status with knowledge regarding self administration of insulin with p-value 0.03 and there was significant association with occupation with knowledge regarding self administration of insulin with p-value 0.047. There was also association between knowledge and practice regarding self administration of insulin with p-value 0.049 Conclusion: Educational and occupational status has influence on knowledge regarding self administration of insulin. Thus it is essential to focus on improving the patient’s knowledge on the related topic so that the participants can enhance their practice as well. Diabetes & Insulin Self Administration education must be imparted by physicians by counselling patients at each follow up visit. Jour of Diab and Endo Assoc of Nepal 2018; 2 (1): 9-16